A new genus of Neocoelidiinae Oman (Hemiptera: Auchenorrhyncha: Cicadellidae) - Marques-Costa, Ana P.; Cavichioli, Rodney R. (Zootaxa, 2006)
A new genus of Neocoelidiinae, Xenocoelidiana gen. nov., and its type-species, Xenocoelidiana ornata sp. nov., are described from the state of Amazonas, Brazil. This new genus is similar to genera with species lacking a distinct carina in the transition between the crown and front (Chinchinota Kramer, Deltocoelidia Kramer, Chinaia Bruner & Metcalf, Xenocoelidia Kramer, and Paraphysiana Chiamolera & Cavichioli). The genus can be distinguished from these other genera mainly by the long coronal suture at the basal half of the crown, the antennal ledges which in lateral view are straight and strongly carinate, and the rectangular clypeus with parallel lateral margins.